Comparative analysis of energy-efficient air conditioner based on brand - Adriansyah Adriansyah; Desmarita Leni; Ruzita Sumiati (Politeknik Negeri Lhokseumawe, 2023)
The availability of numerous air conditioners in the market with various brands and types often leads consumers to be unaware that the purchased air conditioner may be inefficient in terms of energy usage. This research aims to determine the most energy-efficient air conditioner based on the brand of air conditioners available in the market. The research method consists of four stages: data collection, data preprocessing, data analysis, and interpretation of results and conclusions. The data used in this study was obtained from the database of the Directorate General of New, Renewable, and Energy Conservation (EBETKE), which consists of 11 AC brands sold in the market. Data analysis was performed using data distribution analysis techniques, standard deviation calculations, and correlation analysis between variables, such as the Pearson's correlation coefficient. The results of this study show that the AC brand with the highest average efficiency value is Mitsubishi Electric, with a value of 16.36 Energy Efficiency Ratio (EER), while the AC brand with the lowest average efficiency value is GREE, with a value of 5.640 (EER). Each AC brand has a different average efficiency value, with significant variations. From the correlation heatmap results, the AC power does not appear to significantly affect the AC efficiency value, where AC with lower power tends to have higher efficiency values, but there are also AC with high power and high efficiency values. Additionally, the cooling capacity value also appears to have a small effect on the AC efficiency value, where AC with lower cooling capacity tends to have higher efficiency values. However, some AC brands have high cooling capacity values but also have high efficiency values. This study also shows a moderate correlation between the AC efficiency value and the AC's annual energy consumption value, where AC with higher efficiency values tends to have lower annual energy consumption values.